Micropropagation of Possumhaw holly Ilex decidua Walter - Qiansheng Li; Bin Wu; Mengmeng Gu (Technology in Horticulture)
Possumhaw holly (Ilex decidua Walter) is an ornamental shrub or small tree known for its red, orange, or yellow fruits. However, the difficulty of vegetative propagation for specific cultivars or female specimens limits its landscape use. This study aimed to develop an efficient micropropagation method for the mass propagation of female trees. Epicormic shoots were used as explants to establish an initial aseptic culture on woody plant medium (WPM) supplemented with 0.5 mg/L BA. The best results for shoot proliferation, balancing both quantity and quality, were achieved using the Long and Preece (LP) medium with 0.2 mg/L 6-benzylaminopurine (BA), and 0.02 mg/L N-(2-chloro-4-pyridyl)-N-phenylurea (CPPU). High concentrations of BA, CPPU, or zeatin often led to hyperhydricity. Woody plant medium resulted in nutrient deficiency, evidenced by chlorotic leaves on the lower part of regenerated shoots. Conversely, shoots on Driver and Kuniyuki Walnut medium (DKW) exhibited large, thin leaves due to excess nitrogen. For rooting, both in vitro methods using half-strength LP medium with 0.5 mg/L indole-3-butyric acid (IBA) and ex vitro methods with a quick dip in 1 g/L IBA solution achieved 100% rooting success. It is crucial to maintain high humidity for micro-cuttings during the ex vitro rooting. The optimized combinations of plant growth regulators (PGRs) and culture media provide high proliferation and rooting success, facilitating the reliable mass production of uniform female propagules, and ensuring their broader application in landscaping.